PRIORITIZING RISKS IN PAKISTAN’S FISHERIES SECTOR: A STRATEGIC ANALYSIS UTILIZING FUZZY AHP AND IPA METHODOLOGIES - Ana Mehak; Muhammad Mohsin; Muhammad Mobeen Shafqat; Ming-Chang Li (Journal of Animal and Plant Sciences, 2025)
In Pakistan, the fisheries sector plays a vital role in providing livelihood to millions of people and contributing to the national GDP. However, this sector's contribution is far less than its potential. Published literature blames various risks faced by this sector to be responsible for this occurring. However, it does not compare, and rank risks based on their importance for directional management, which can help improve this prevailing situation. In this regard, the present study represents a pioneering and comprehensive investigation. Primary data was acquired from 317 survey respondents representing various fisheries stakeholders from Balochistan between 13 November 2023 and 9 February 2024. Fuzzy Analytic Hierarchy Process (fuzzy AHP) and Importance Performance Analysis (IPA) were utilized as statistical analysis tools. According to this study, the main risks confronted by the fisheries sector in Balochistan revolve around management risk (0.431), economic risk (0.212), and occupational risk (4.861). The most significant sub-risks affecting this sector are intense fishing (0.114), problems related to trade (0.088), and excessive discard rate (0.068). There is a dire need to focus on significant risks to improve the fisheries sector performance. Moreover, survey respondents also reported low levels of risk perception and suggested improving the prevailing situation by implementing rewards systems and performance evaluation programs.
Keywords: Fisheries; Management; Performance; Fuzzy AHP; IPA; Pakistan